Characteristics and clinical needs of young tertiary students attending a specialist mood disorders clinic. (June 2023) - O'Gorman, Kieran M; Schmaal, Lianne; Ratheesh, Aswin; Habib, George; Tokatlidis, Orania; Jackson-Simpson, Jennifer; Cotton, Sue M; Rice, Simon M
Objective: To investigate the clinical characteristics of tertiary students and non-students attending a specialist clinic for severe mood disorders. Method: Medical record audit of clients discharged from the Youth Mood Clinic (YMC). Data extracted included depressive symptomatology, suicidal ideation, self-harm, suicide attempt, tertiary education engagement, drop-out and deferral. Results: Data from 131 clients ( M age = 19.58 years, SD = 2.66) were analysed, including 46 tertiary students. Relative to non-students, at intake, tertiary students reported more severe depressive symptomatology ( d = 0.43). They were more likely to experience suicidal ideation at intake ( V = 0.23), and during treatment ( V = 0.18). Tertiary students were also more likely to be living separately to their family of origin ( V = 0.20) but were less likely to have experienced parental separation ( V = 0.19). 21.73% of tertiary students dropped out or deferred study during care. Conclusion: In this cohort, those engaged in tertiary education experience more severe depression and more commonly experienced suicidal ideation. These young people require targeted support for their mental health while they undertake tertiary education.